How Should Customers Be Integrated for Effective Interorganizational NPD Teams? An Input–Process–Output Perspective1. Issue 3 (16th January 2014) - Stock, Ruth Maria
<x xml:space="preserve">Abstract</x> Interorganizational new product development (NPD) teams with business customers are rapidly becoming more prevalent; yet the drivers of such cooperations at the team level remain unclear to practitioners and researchers alike. This study proposes an input–process–output model in which various characteristics of interorganizational teams affect NPD team effectiveness through the mediating construct of NPD team cooperation. Furthermore, various moderators, reflecting the supplier's dependence on the customers (customer power and customer participation) and the supplier's environmental uncertainty (market dynamism and technological turbulence), affect the strength of the underlying relationships. The results show that customer power positively affects the relationship between intrapersonal team characteristics and team cooperation. In addition, a negative moderation occurs in interpersonal characteristics. Customer participation exhibits opposing moderating effects. Regarding the supplier's environmental uncertainty, market dynamism and technological turbulence strengthen the relationships under consideration.